Pertukaran Anggota dan Pemimpin (Leader Member Exchange) - Khoirul Anam; Javier Rizqi Baiturrahman; Bagus Alamsyah Bahari; Moch. Isa Anshori (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
This study aims to provide insights and understanding of the importance of the relationship between leaders and members in creating a healthy and productive work environment, as well as assisting organizations in designing more effective leadership development programs. The study utilizes a literature review method to compile research frameworks based on relevant previous studies. The findings of the study indicate that the quality of the relationship between leaders and members significantly influences organizational performance. A better relationship between leaders and members has positive impacts on employee performance, innovative attitudes, work ethics, employee loyalty, job engagement, employee performance, organizational citizenship behavior, effective communication, job satisfaction, and significant reduction in turnover intention. This highlights the importance for organizations to pay attention to the quality of the relationship between leaders and members in creating a healthy and productive work environment. Additionally, organizations should also focus on leadership development that enhances the quality of the relationship between leaders and members.